CLUSTERING OF HIGH-TECH INDUSTRIAL PRODUCTION: FACTORS AND TRENDS - Napolskikh, Dmitry (Journal of Applied Engineering Science, 2018)
The purpose of the study is to identify trends and future models for the development of regional industrial clusters in the new technological order. Paper deals with the dynamics of the formation of industrial clusters, the main regularities of the development of high-tech industries are revealed. Particular attention is given to localization of high-tech industries within the framework of regional industrial clusters; scientific novelty contains a model of inter-sectoral interaction in the conditions of the innovation economy. The result of the analysis shows, that successful cluster initiatives combine a developed innovative core, an essential industrial basis and a significant number of small and medium-sized forms of innovative entrepreneurship.